Effect of date-palm wastes as a substrate on tomato yield and number - M. Shirani (ՀՀ ԳԱԱ հրատ.)
The aim of this study was the using of Date-Palm waste as a substrate on tomato yield and number. The research was conducted in a completely block randomized design with 4 replications in three experiments. Հետազոտման նպատակն է՝ ուսումնասիրել, որպես սննդամիջավայր օգտագործվող փյունիկյան արմավենու թափոնների ազդեցությունը տոմատի պտուղների քանակի և բերքատվության վրա: Целью данного исследования является изучение влияния размера фракционных частиц и времени компостирования отходов финиковых пальм на урожайность и количество плодов томата.
Keywords: Agriculture; Plants